Analysis of Production Planning Problem in Palembang's Jumputan Industry Using Earlier Deadline First Algorithm - Shabila Fitri Aulia; Muhammad Izman Herdiansyah; Dedy Syamsuar; Ahmad Syazili (Universitas Bina Darma, 2022)
Palembang is one of the big cities that has jumputan cloth as one of its characteristics. Palembang has many areas where craftsmen produce jumputan fabrics, one of which is in the area of Tuan Kentang. Many craftsmen in the area have not used existing technological developments s there are several problems that occur such as in the scheduling process. Scheduling issues are important because craftsmen usually produce fabrics based on the history of the previous year so when there is an order outside the available stock, there are often delays in the order being completed. In this study, researchers took the initiative to solve this problem by analyzing the scheduling process using the Earlier Deadline First (EDF) algorithm. This algorithm serves to help craftsmen determine when each manufacturing process is carried out and helps craftsmen to determine which orders to work on first based on the deadline. The results obtained after the implementation of this algorithm prove that the algorithm can minimize the occurrence of order delays and successfully prioritize which orders should be done so as to minimize the occurrence of delays in orders which creates a decrease in the level of consumer confidence in craftsmen.